The Effect of a Rotating Medium on Bulk Acoustic Wave Polarization: From Theoretical Considerations to Perspective Angular Motion Sensor Design - Durukan, Yasemin; Shevelko, Michail; Peregudov, Aleksandr; Popkova, Ekaterina; Shevchenko, Sergey (Sensors (Basel, Switzerland), 2020)
We study the effects of medium rotation on bulk acoustic wave (BAW) propagation. For a theoretical analysis of the BAW propagation characteristics, a motion equation for the plane harmonic waves propagating orthogonal to the rotation axis of the propagation medium was analytically resolved. We found that during medium rotation, the polarization of the waves becomes elliptical with the ratio of the polarization ellipse axes explicitly proportional to the angular velocity of the medium rotation, thereby opening the way for the design of sensitive elements (SE) for perspective angular motion sensors (AMS). Next, an analytical dependence of the SE informative parameter on the Poisson’s ratio of the acoustic duct material was obtained. The rotation effect on the dispersion of BAW propagation velocity was studied. Two approaches to the perspective SE design were proposed. An experimental study of a specially designed test assembly and SE model demonstrated high correlation with theoretical predictions and provided an estimate of a potential SE. Therefore, we believe that the study of acoustic wave propagation under nonclassical conditions is a promising direction for prospective solid-state AMS on based on BAW polarization effects design.